1979
DOI: 10.1128/aem.38.5.806-810.1979
|View full text |Cite
|
Sign up to set email alerts
|

Role of bovine serum albumin in the nutrition of Mycobacterium tuberculosis

Abstract: Bovine serum albumin promotes the growth of small inocula ofMycobacterium tuberculosis in media containing unesterified fatty acids. Albumin binds fatty acids present in concentrations toxic for the organisms. In the present study, additional roles of albumin were investigated. When present in a basal medium, fatty acid-free albumin could be utilized by M. tuberculosis as a sole source of carbon. Since albumin could not substitute for the amino acids in basal medium as a nitrogen source, it was concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Also, oleic acid helps in supplementing the nutritional requirements of Mtb. The addition of Tween 80 and oleic acid might be counterproductive, as unesterified fatty acids from Tween 80 are lethal to Mtb at concentrations required for proper dispersion of aggregates [ 31 ]. Davis and Dubos observed that BSA provides a protective effect against this toxicity [ 21 ], and since then, it has been standard practice to use BSA as a supplement for culturing Mtb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, oleic acid helps in supplementing the nutritional requirements of Mtb. The addition of Tween 80 and oleic acid might be counterproductive, as unesterified fatty acids from Tween 80 are lethal to Mtb at concentrations required for proper dispersion of aggregates [ 31 ]. Davis and Dubos observed that BSA provides a protective effect against this toxicity [ 21 ], and since then, it has been standard practice to use BSA as a supplement for culturing Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been proposed that fatty acid-free BSA (or BSA fraction V) helps in the binding of fatty acids and helps increase the wetting of the surface of bacteria, and increases access to nutrients such as oleic acid. Besides this, BSA may have a nutritional effect on Mtb, though not by supplying amino acids [ 21 , 31 ]. Significantly, DTT reduces disulfide bonds in BSA and induces the formation of microaggregates [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant M. abscessus growth enhancement was observed in the presence of HSA up to 32 mg/mL (3.2% in the medium). It was previously reported that BSA promotes M. tuberculosis growth by delivering fatty acids as carbon sources . The iron-poor medium in our study contains 0.5% glycerol and 0.05% Tween 80.…”
Section: Discussionmentioning
confidence: 89%
“…It was previously reported that BSA promotes M. tuberculosis growth by delivering fatty acids as carbon sources. 45 The iron-poor medium in our study contains 0.5% glycerol and 0.05% Tween 80. Hence, glycerol and Tween 80 bound to HSA in an iron-poor medium could serve as carbon sources, promoting the growth of the slow-growing mycobacteria, but not the more rapid-growing M. abscessus.…”
Section: ■ Discussionmentioning
confidence: 93%
“…Thus, some studies have reported that the detoxification of oxidative stress during culture is one of the key mechanisms through which VBNC bacteria are resuscitated (Mizunoe et al, 2000;Imazaki and Nakaho, 2009). Some mycobacterial culture media contain bovine serum albumin (BSA) and BSA on mycobacterial culture has been considered to be growthsupporting agent that is involved in detoxification by the absorption of free fatty acid and other growth-arresting agents that are spontaneously generated during culturing (Davis and Dubos, 1947;Dubos, 1947;Lynn et al, 1979). For this reason, the mycobacterial culture media that are most frequently used at the present time are protein-containing systems, such as Middlebrook 7H series or Dubos medium.…”
Section: Introductionmentioning
confidence: 99%